SALIB KRISTUS SEBAGAI SIMBOL KEKERASAN UMAT YAHUDI (Studi Teologis Matius 26:1-5 Diperhadapkan dengan Kondisi Indonesia Masa Kini) - Ibelala Gea (Jurnal Teologi Cultivation, 2019)
AbstractThe research in this article aims to explain that theologically, the crucifixion of Christ as a symbol of the violence of the Jews hide behind the Roman law, and confronted with the condition of present-day Indonesia.To explain the violence that comes from Matthew 26: 1-5 as a basis for the discussions were enriched by a number of violence-related references.The results showed that violence as the imposition of the will to achieve the goals, whether individuals, groups and institutions.Violence tangible crucifixion of Jesus was hiding behind the guise of religious Jews, laden with engineering, which is the real Jesus was not guilty of what is charged to him.The Roman government represented Pilate dare not uphold justice, it can be called that trial and the verdict against Jesus is gray as a result of a compromise and government conspiracy with the leader of the majority religion, the Jewish religion.Violence in Indonesia, including violence against women, children and political violence as a sign of not respecting others.Lodging in the political violence, often triggered by the politicization of religion as a vehicle to achieve the goal by mobilizing the number of people that fanaticism and radicalism.Any violence is not in accordance with the will of God who loves the whole humanKeywords: Cross of Christ And Violence of Jewish People